Molecular imprinted polymer-based potentiometric approach for the determination of carvedilol and ivabradine hydrochloride in dosage form, spiked human plasma and in presence of their oxidative degradates - Nermine V. Fares; Haitham A. El Fiky; Dina A. Ahmed; Maha F. Abd El Ghany; Amr M. Badawey; Mahmoud A. Tantawy (BMC Chemistry)
Abstract Carivalan® pharmaceutical formulation, which includes carvedilol and ivabradine hydrochloride, is commonly prescribed for alleviating pain associated with angina. Solid contact ion-selective electrodes with wide range of applications have been developed for analysis of these two active ingredients. Those types of electrodes have common drawbacks. Aside from development of aqueous layer, the incorporated ion exchanger in plasticized membrane is usually unable to differentiate in sensing between two similarly charged lipophilic organic ions. These flaws impeded simultaneous quantification of carvedilol and ivabradine hydrochloride in their dosage form. First, attempts were made to stabilize possible signals by synthesizing hydrophobic multiwall carbon nanotubes-based carbon paste. Precipitation polymerization was used to create molecular imprinted polymers (MIPs) for each drug. MIPs’ graved cavities serve as artificial host-tailored receptors that are able to recognize and bind to individual drugs. Carvedilol MIP-based sensor showed Nernstian slope of 55.30 mV/decade while the corresponding value for ivabradine one was 55.50 mV/decade. The respective LODs were 7.0 × 10− 8 M and 6.0 × 10− 7 M. Interference from excipients of pharmaceutical formulation, common plasma ions, and possible oxidation byproducts was not witnessed, permitting direct and simultaneous measurement of carvedilol and ivabradine in their tablet solution and spiked human plasma. Furthermore, the proposed technique was compared favorably with the official titrimetric and reported spectrophotometric methods for analyzing carvedilol and ivabradine, respectively.